The influence of emotions on science teaching: a case study with three early childhood education teachers - Praderio Gaias, Florencia Natalia; Furman, Melina; Luzuriaga, Mariana; Borrego, Emilio Costillo; Ayuso Fernández, G. Enrique (Frontiers in Education, 2024)
Teaching science in early childhood education (ECE) is crucial for fostering essential scientific thinking skills, which are vital for young learners’ development and formative trajectories. While this educational level presents exciting opportunities for integrating science teaching, it also poses challenges related to teachers ́ cognitive, pedagogical, and emotional constraints. Recognizing the pivotal role of teachers’ emotions in shaping their practices, we aim to specifically examine the influence of teachers’ emotions on science teaching in ECE, an area that remains underresearched. We conducted a multiple case study involving three ECE teachers in La Plata, Argentina, who demonstrated a strong interest in improving their pedagogical practices despite acknowledging their difficulties and insecurities in teaching science. We explored their emotions and how they relate to science lesson planning and implementation through surveys, in-depth interviews, and observations. Data collection was designed in three stages: pre-active, interactive, and post-active teaching. First, we surveyed the range of negative and positive emotions that teachers experienced toward sciences, rooted in their personal and formative prior experiences, and examined how these emotions influenced their planning (pre-active stage). Subsequently, we investigated the emotions associated with science teaching in the interactive stage and recorded classroom observations to document how they implemented their plans. Finally, we conducted in-depth interviews with the teachers while they watched the recorded class videos, allowing them to reflect on their decision-making and implementation characteristics (post-active stage). Our findings reveal a dichotomy: negative emotions derived from past experiences reduce engagement, while positive emotions enhance motivation and enrich the learning environment. Negative emotions arising from the implementation of science activities in real classroom contexts may lead to canceled classes, whereas positive emotions foster persistence and optimism. We discuss the significance of emotional awareness in teaching practices, emphasizing the importance of understanding and managing negative emotions through teacher training and professional development programs. This approach can enhance teacher confidence and satisfaction, ultimately contributing to improved early childhood science education.